EANS, European Academy of Nursing Science - (:unkn) unknown (My University, 2026)
EANS has been in existence since 1998: a short history by Professor Rosemary Crow, EANS founding President, is provided here: History-of-EANS. The purpose of the Academy is to be the scientific community in Europe providing inspiration, collaboration and academic leadership in nursing. We do this by sustaining a forum of European nurse scientists who are developing and promoting knowledge in nursing through research and scholarly achievement in the pursuit of excellence.